Key sectors in the Moroccan economy: An application of input-output analysis - Said Tounsi; El hadj Ezzahid; Aicha El Alaoui; Abdelaziz Nihou (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
The exploration of the structural features and sectoral interdependences of and in an economy is fundamental for the understanding of its modes of functioning and of its transformations over time. Input-output analysis is largely used to fulfill this objective. Furthermore, information provided by the Leontief inverse matrix is useful for the identification of key sectors. This identification may guide policy makers in setting an adequate industrial strategy. In this paper, the classification of productive sectors is performed by using the Unweighted Rassmussen Approach. The ordering of sectors depends on the intensity of their links with other sectors. Two results ought to be highlighted. First, key sectors of the Moroccan economy (sectors that are classified in category II) reduced to two sectors in 2007 instead of four sectors in 1998. Second, the ordering of sectors is highly sensitive to the precision of the data and to the year in which the classification is realized.
Keywords: C67; D57; 330; input-output analysis; backward linkages; forward linkages; unweighted Rassmussen approach; Morocco; Branche; Makroökonomischer Einfluss; Input-Output; Marokko